Coordination between photorespiration and carbon concentrating mechanism in Chlamydomonas reinhardtii: transcript and protein changes during light-dark diurnal cycles and mixotrophy conditions. - Tirumani, S.; Gothandam, K.M.; J Rao, Basuthkar (Protoplasma, 2019)
Carbon concentrating mechanism (CCM) and photorespiration (PR) are interlinked and co-regulated in Chlamydomonas reinhardtii, but conditions where co-regulation alters are not sufficiently explored. Here, we uncover that PR gene transcripts, like CCM transcripts, are induced even in the dark when both processes are not active. Such diurnal cycles show that transcript levels peak in the middle of 12 h day, decline by early part of 12-h dark followed by their onset again at mid-dark. Interestingly, the onset in the mid-dark phase is sensitive to high CO2, implying that the active carbon sensing mechanism operates even in the dark. The rhythmic alterations of both CCM and PR transcript levels are unlinked to circadian clock: the "free-running state" reveals no discernible rhythmicity in transcript changes. Only continuous light leads to high transcript levels but no detectable transcripts were observed in continuous dark. Asynchronous continuous light cultures, upon shifting to low from high CO2 exhibit only transient induction of PR transcripts/proteins while CCM transcript induction is stable, indicating the loss of co-regulation between PR and CCM gene transcription. Lastly, we also describe that both CCM and PR transcripts/proteins are induced in low CO2 even in mixotrophic cultures, but only in high light, the same being attenuated in high CO2, implying that high light is a mandatory "trigger" for CCM and PR induction in low CO2 mixotrophy. Our study provides comprehensive analyses of conditions where CCM and PR were differently regulated, setting a paradigm for a detailed mechanistic probing of these responses.